‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (The Australian and New Zealand journal of criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.